Kepatuhan terhadap Protokol Kesehatan oleh Tenaga Teknis Kefarmasian di Apotek - Fathul Muin; Anna Wahyuni Widayanti; Yayi Suryo Prabandari (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
Pharmacy technician as health workers in pharmacies have high risk of transmitting the COVID-19 virus. They often have direct contact to public or COVID-19 patients who come to pharmacies. This study aimed to determine the compliance level of pharmacy technician to the COVID-19 health protocols and its correlations to the level of knowledge, organizational-environment and self-efficacy. This study was designed descriptive correlational used self-administered questionnaire to collect data with cross sectional study. The participants were selected with simple random sampling among pharmacy technician who worked in community pharmacies in Sleman. A total of 98 pharmacy technician were participated in this study. The compliance levels were divided into low, medium and high. Most participants were in medium level of compliance (61.2%), followed by high level (35.7%) and only 3.1% participants in low level. Data analysis was carried out by cross-sectional and statistical test with SPSS by comparing the three factors to the level of compliance. Statistical tests on organizational-environmental factors and self-efficacy showed a significance value (p<0.05) with a Pearson Correlation value of 0.393 and 0.350. The level of knowledge showed not significance value (p>0.05) with a Pearson Correlation value of 0.152. There was a correlation between organizational-environmental factors and self-efficacy with the the compliance level of pharmacist assistants to the COVID-19 health protocols. While the level of knowledge showed results that there is no correlation.